2022
DOI: 10.1108/jme-12-2021-0225
|View full text |Cite
|
Sign up to set email alerts
|

Supporting educators’ professional learning for equity pedagogy: the promise of open educational practices

Abstract: Purpose In the research literature relevant to open educational practices (OEP), the terms “students” or “learners” often refer to individuals engaging in formal study. This study aims to broaden the conception of learners to include those who engage with continuing professional development or professional learning. The study focussed on one intersection of OEP with equity pedagogy for these learners. Design/methodology/approach Guided by transformative approaches to knowledge, the research is qualitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…6;Jisc, 2021); however, these have been primarily developed in an international context. There exists an identified gap in practical support at the nexus of OER and inclusive design in Australia (Lambert & Fadel, 2022;Stagg et al, 2023;Tualaulelei & Green, 2022). In response, in 2022, a LATN-funded Fellowship project proposed to develop a practical resource to empower Australian open education practitioners to create and evaluate OER which influence greater diversity and inclusion in pedagogical practice.…”
Section: Background and Libraries Of The Australian Technology Networ...mentioning
confidence: 99%
See 1 more Smart Citation
“…6;Jisc, 2021); however, these have been primarily developed in an international context. There exists an identified gap in practical support at the nexus of OER and inclusive design in Australia (Lambert & Fadel, 2022;Stagg et al, 2023;Tualaulelei & Green, 2022). In response, in 2022, a LATN-funded Fellowship project proposed to develop a practical resource to empower Australian open education practitioners to create and evaluate OER which influence greater diversity and inclusion in pedagogical practice.…”
Section: Background and Libraries Of The Australian Technology Networ...mentioning
confidence: 99%
“…OER are "learning, teaching and research materials in any format and medium that reside in the public domain or are under copyright that have been released under an open license, that permit no-cost access, re-use, re-purpose, adaptation and redistribution by others" (UNESCO, 2019). Many studies have shown that OER can help to rebalance representation by removing the traditional publishing 'gatekeeper' and enabling flexible interpretations of the textbook (Herbert, Clinton-Lissell & Stupinsky, 2022;Lambert & Fadel, 2022;Paskevicius, 2017;Tualaulelei & Green, 2022). However, the reality is OER alone cannot achieve this goal because OER itself is not the goal.…”
Section: Introductionmentioning
confidence: 99%